Innovative Clinical Supervision for Excellence in Pedagogy: An Outcome-Based Project in Improving the Attributes and Performance Level of K to 12 Teachers - Año, Francis Ryan (JPAIR Institutional Research, 2020)
The K to 12 basic education program brought reforms in the Philippine educational system constructively aligned with the 21st-century learning revolution in the ASEAN and international communities. This descriptive-evaluative correlational research, as funded by the DepED Basic Education Research Fund (BERF), investigated the improvement on the attributes and teaching performance level of the seventeen (17) purposively selected K to 12 teachers from the clustered schools through innovative clinical supervision. The researcher used a validated self-made questionnaire to gather the data and, statistically, analyzed using weighted mean, Pearson r, and t-test. Results revealed that the teachers attained a proficient level in the K to 12 attributes advanced level in the teaching performance, and the Innovative Clinical Supervision for Excellence in Pedagogy (ICSEP) Project was highly effective. Significant correlations emerged between the K to 12 attributes of teachers and the effectiveness of the ICSEP project and the teaching performance level and the effectiveness of the ICSEP project. A significant difference existed between the pre-and post-survey results on the K to 12 attributes of the teachers and their pre-and post-clinical observation results on the teaching performance of the K to 12 teachers. Thus, the ICSEP project has a positive correlation and impact on the improvement of the attributes and teaching performance level of the teachers.